IC 8943 Interim Performance Specifications For Transducer Modules Used With The Bureau Of Mines Intrinsically Safe Mine Monitoring System - Carbon Monoxide, Methane, And Air Velocity - J. E. Chilton (The National Institute for Occupational Safety and Health (NIOSH), 1983)
Interim performance specifications are presented for carbon monoxide, methane, and air velocity transducers used in the Bureau of Mines intrinsically safe mine monitoring system. These specifications give quantitative values or qualitative descriptions of the transducers, including environmental parameters and monitoring system measurement and maintenance requirements as recommended by the Bureau of Mines. Commercially available transducer modules and prototype modules are listed together with selected characteristics.